Biorenal Effects of the Polyherbal (Andrographis paniculata, Annona muricata, Zingiber officinale) Aqueous Extract on Wistar Rats - Gabriel, Benjamin Ogunma; Osawese, Ehonwa Lisa; Oshomoh, Emmanuel (Darul Yasin Al Sys, 2024)
There has been a reliance on medicinal plant parts and their extracts for the prevention and treatment of diseases throughout history. Toxicological studies have now shown concern on the unavailability of standard dosage for the treatment of these substances that causes for concern. This study evaluated the bio-renal safety of the polyherbal aqueous extract of in Wistar rats. The aqueous extracts were obtained using standard methods. A total of 25 adult rats were used and administered to the tested groups for 28 days. Kidney function test was carried out together with histopathological evaluations of the kidneys of the rats. The results obtained showed that urea, creatinine, Na+, K+, Cl- and HCO- concentrations across 25-57 mg/dl, 0.1-0.8 mg/dl, 134-142 μmol/l, 4.4-4.9 μmol/l, 96-103 μmol/l and 21-28 μmol/l, had no significant difference at graded doses of the treatment groups respectively. These results were in the normal range when compared with the control. The histopathological study of the kidney tissues showed normal architectural structures with visible renal corpuscles and distinct tubules. In conclusion, the polyherbal aqueous extract had no adverse effects across the tested animals at graded doses. However, further research is recommended for drug evaluation.